Il-6 and type 1 diabetes mellitus: t cell responses and increase in il-6 receptor surface expression - Karina Braga Gomes Borges (2017)
Type 1 diabetes mellitus (T1D) is an autoimmune disease characterized by beta cell destruction, associated with cellular infiltration and inflammatory responses in the islets of Langerhans. The cellular components of this infiltrate include monocytes, macrophages, CD4+ and CD8+ T cells, and the balance between Th1 and Th2 cells is crucial in the pathogenesis of this disease. Cytokines play important role in the development and activation of immune cells, since they act as cell-signaling molecules, especially in autoimmune diseases, including T1D. Moreover, cytokines may serve as additional biomarkers of T1D. Cytokines may also provide valuable information about the pathways involved in the regulation of T1D processes. Interleukin-6 (IL-6), a multifunctional cytokine, is secreted by T cells and macrophages to stimulate immune response during inflammation and infection. Indeed, this cytokine is involved in the inflammatory response associated with insulin-resistant states.